The bondage of the affections: willing, feeling, and desiring in Luther's theology, 1513-1525 - Zahl, Simeon (University of Notre Dame Press, 2015)
This essay examines the place of affectivity and emotion in Martin Luther's early theology 1513-25. After a critical discussion of the terminological complexities involved in analysing affectivity and the related category of desire in Luther's Latin writings, it draws on a wide range of Latin and German texts to make an original argument about the origins of Luther's theology of the bondage of the will. It is shown that in developing this theological category Luther regularly used empirical/experiential arguments based on own personal experience of the insuperability of certain sinful affections, and that it is Luther's empirical-theological reflections on the domination of the ratio by the affections – rather than philosophical arguments about necessity and determinism or exegetical arguments from classic prooftext – that is probably the most important influence behind the doctrine. The article concludes by suggesting (i) that this finding has important implications for understanding Luther's thought in general, as it problematizes his later critique of experience-based doctrinal arguments, and (ii) that Luther scholarship has in recent decades tended to read the early Luther in light of the later Luther, with problematic results.